2017
DOI: 10.1021/acs.jafc.7b03093
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Coated Cinnamon/Oregano-Loaded Solid Lipid Nanoparticles to Augment 5-Fluorouracil Cytotoxicity for Colorectal Cancer: Extract Standardization, Nanoparticle Optimization, and Cytotoxicity Evaluation

Abstract: This study aimed to coat lipid-based nanocarriers with chitosan to encapsulate nutraceuticals, minimize opsonization, and facilitate passive-targeting. Phase one was concerned with standardization according to the World Health Organization. Qualitative analysis using liquid chromatography-high-resolution mass spectrometry (LC-HRMS/MS) investigated the active constituents, especially reported cytotoxic agents. Cinnamaldehyde and rosmarinic acid were selected to be quantified using high-performance liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…On the contrary, EA extract reduced significantly cell viability (<60% compared to control group; Figure 6). This result is consistent with the findings by Kamel, Khalil, Rateb, Elgendy, and Elhawary (2017), who observed a reduction of HCT116 cell viability after challenging the cells with an ethanol Origanum extract, that exerted antiproliferative effects at concentrations < 100 µg/ml. Conversely, all extracts did not modify spontaneous cell migration, in wound healing test, thus excluding any effect on migration and invasion capacities of HCT116 human colon cancer cells (Figure 7).…”
Section: Pharmacological Studiessupporting
confidence: 93%
“…On the contrary, EA extract reduced significantly cell viability (<60% compared to control group; Figure 6). This result is consistent with the findings by Kamel, Khalil, Rateb, Elgendy, and Elhawary (2017), who observed a reduction of HCT116 cell viability after challenging the cells with an ethanol Origanum extract, that exerted antiproliferative effects at concentrations < 100 µg/ml. Conversely, all extracts did not modify spontaneous cell migration, in wound healing test, thus excluding any effect on migration and invasion capacities of HCT116 human colon cancer cells (Figure 7).…”
Section: Pharmacological Studiessupporting
confidence: 93%
“…Zhang et al modified chitosan by using heptamethine and folate for photodynamic treatment and tumor-imaging [ 54 ]. Kamel et al modified chitosan by encapsulating oregano and cinnamon within chitosan in combination with 5-fluorouracil as an effective agent for tumors [ 55 ]. Lin et al studied chitosan derivatives and found that chitosan-based nanocarriers used for co-delivery of genes and drugs were redox responsive [ 56 ].…”
Section: Chitosan-based Nanoparticlesmentioning
confidence: 99%
“…Kamel et al prepared chitosan-coated cinnamon/oregano-loaded solid lipid nanoparticles to augment 5-FU cytotoxicity for colorectal cancer. 21 Pretel et al utilized nanoprecipitation and solvent evaporation methods to optimize poly( d , l -lactide-co-glycolide) nanoparticles for the delivery of 5-FU. 22 In Sharma et al’s investigation, 5-FU was conjugated to PEG-anchored recombinant human serum albumin nanoparticles to improve the pharmacokinetics and therapeutic profiles.…”
Section: Introductionmentioning
confidence: 99%